2000
DOI: 10.2307/2656868
|View full text |Cite
|
Sign up to set email alerts
|

The questionable relationship of Montinia (Montiniaceae): evidence from a floral ontogenetic and anatomical study

Abstract: The systematic position of Montiniaceae remains uncertain: a relationship with Cornales has been suggested on phytochemical and embryological evidence, while molecular data point to a relationship with Solanales. We investigated the floral development and anatomy of the South African Montinia caryophyllacea to add a new set of characters for clarifying the systematic position of the family Montiniaceae. Pistillate inflorescences show a higher degree of reduction than staminate, with flowers set terminally on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…and Kaliphora Hook. f., are described as cymose (Ronse Decraene et al, 2000; Stevens, 2001 onward). The only genus of Hydroleaceae, Hydrolea L., has cincinni, a type of scorpioid cyme (Watson and Dallwitz, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…and Kaliphora Hook. f., are described as cymose (Ronse Decraene et al, 2000; Stevens, 2001 onward). The only genus of Hydroleaceae, Hydrolea L., has cincinni, a type of scorpioid cyme (Watson and Dallwitz, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…In Paracryphiales, flowers appear choripetalous, but development has not been studied (Endress 2010a). For the evolution of sympetaly and fluctuations between sympetaly and choripetaly in basal asterids, see also Endress (1997a) and Ronse Decraene et al (2000).…”
Section: New Family Positions With Drastic Changesmentioning
confidence: 99%
“…Some comparative studies of floral ontogeny examining interfamilial relationships have found contrasting evidence, or no evidence, for hypotheses derived from molecular analyses (e.g. Caris et al, 2000Caris et al, , 2002Ronse de Craene et al, 2000;Caris and Smets, 2004;Erbar et al, 2005). However, sequence-based results have found support from developmental surveys (e.g.…”
Section: The Floral Development Perspectivementioning
confidence: 99%